REAKSI PASAR MODAL SEBELUM DAN SESUDAH PENGUMUMAN KEBIJAKAN CUKAI ROKOK: STUDI PADA ABNORMAL RETURN, TRADING VOLUME ACTIVITY, DAN VOLATILITAS HARGA SAHAM EMITEN TEMBAKAU 2020–2024 - Yuslinda Nasution l; Alina Rohma (Jurnal Satya Mandiri Manajemen dan Bisnis, 2026)
This study aims to analyze the capital market reaction to the announcement of the cigarette excise tax increase using an event study method. Market reaction is measured using abnormal return indicators, trading volume activity (TVA), and stock price volatility in cigarette segment corporations listed on the Indonesian capital market during 2020–2024. This study uses an 11-day event window, from t-5 to t+5 around the policy announcement date. The research approach used is quantitative, applying the classical assumption test, paired sample t-test, and the Wilcoxon test. The sample was determined using purposive sampling and involved two tobacco companies. Data were obtained from Indonesia Stock Exchange publications and the official websites of the companies concerned. The results indicate that, in general, there were no significant differences before and after the excise tax increase announcement in terms of abnormal returns or trading volume activity. However, in 2022, a significant difference was found in trading volume activity. Furthermore, descriptively, stock price volatility exhibited a fluctuating pattern, indicating market uncertainty regarding the policy.